The Relationship Between the Environmental Tax Revenues and the Greenhouse Gas Emission in Romania - Liviu Andrei Toader; Florentina Chitu; Dorel Mihai Paraschiv (Ovidius University Annals: Economic Sciences Series, 2023)
In order to meet the Paris Agreement target, mankind must reduce greenhouse gas emissions to unprecedented levels by 2030. Major global shifts towards a low-carbon economy and transformations of financial systems in each country are expected, changing new financial structures and processes, involving national governments, central and commercial banks, investors and financial actors. Romania has among the lowest environmental tax revenues as a percentage of GDP, according to Eurostat, and energy taxes are the most important category of environmental taxes, followed by transport taxes, pollution and resource exploitation taxes, etc. In this paper we aim to see the relationship between environmental tax revenues and greenhouse gas emissions in Romania, using correlation and regression analysis. The results of the study validate the main hypothesis, that is a strong inverse significant relationship between the two variables analysed and serve as a basis for further research on environmental taxes and charges in a given country (their amount and percentage of the country's GDP) and the evolution of greenhouse gas emissions (progress towards their reduction).